2020
DOI: 10.1101/2020.05.11.20098418
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spread of the Novel Coronavirus (SARS-CoV-2): Modeling and Simulation of Control Strategies

Abstract: The coronavirus disease 2019 is spreading throughout the world and all healthcare systems are loaded beyond its capacity. The virus is named as SARS-CoV-2. In this situation, rational decisions need to be made on how the care is provided for patients with COVID-19. The Incidence report, general symptoms and readily available testing kits, different control strategies, the basic compartmental model, and some of the current research on the epidemiology of the disease are discussed and previously published model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…[15,16,17,18,19,20] A control strategy simulation suggested that tightly regulated social distancing can reduce the number of cases during peak time. [21] Both New Zealand and Australia have reduced COVID-19 spreading by a government-driven social distancing strategy. [22] On the other hand, Sweden's government is not tightly recommending a social distancing strategy.…”
Section: Social Distancingmentioning
confidence: 99%
“…[15,16,17,18,19,20] A control strategy simulation suggested that tightly regulated social distancing can reduce the number of cases during peak time. [21] Both New Zealand and Australia have reduced COVID-19 spreading by a government-driven social distancing strategy. [22] On the other hand, Sweden's government is not tightly recommending a social distancing strategy.…”
Section: Social Distancingmentioning
confidence: 99%
“…A deterministic compartmental model that incorporates critical care patients and hospitalisations, with a time (and lockdown) dependent infectious contact rate parameter, is presented in [24]. Here, other model parameters are fixed, based upon examples in the literature, and the initial infection rate and number infected are fitted to real-world mortality and observed new cases data.…”
Section: Covid-19 Modelsmentioning
confidence: 99%